2022
DOI: 10.3389/fbioe.2022.823557
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Anterior Center-Edge Angle on Acetabular Stress Distribution in Borderline Development Dysplastic of Hip Determined by Finite Element Analysis

Abstract: Background: The joint with hip dysplasia is more likely to develop osteoarthritis because of the higher contact pressure, especially in the socket. The lateral center-edge angle (LCEA) is the major indicator for hip dysplasia via radiography. However, the pathological conditions of LCEA angles in the range of 18°–25° are still controversial, which challenges precise diagnosis and treatment decision-making.Objective: The purpose of this study is to investigate the influence of anterior center-edge angle (ACEA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…A more favorable angle provides improved joint congruency and stability, distributing forces more evenly across the joint. [18,48,49] Three studies exploring the role of Center Edge Angle (CEA) to evaluate hip joint contact stress, but did not nd any consistent effect between the degree of CEA and hip contact stress. Furthermore, there was no evident correlation between changes in the CEA and hip contact stress (Fig.…”
Section: Center Edge Angle (Cea)mentioning
confidence: 99%
“…A more favorable angle provides improved joint congruency and stability, distributing forces more evenly across the joint. [18,48,49] Three studies exploring the role of Center Edge Angle (CEA) to evaluate hip joint contact stress, but did not nd any consistent effect between the degree of CEA and hip contact stress. Furthermore, there was no evident correlation between changes in the CEA and hip contact stress (Fig.…”
Section: Center Edge Angle (Cea)mentioning
confidence: 99%
“…However, the lack of anterior hip coverage can cause symptoms around the hip joint as well as lack of lateral coverage [2][3][4]. Following the increasing understanding of the 3D morphology of the hip joint, an increasing emphasis has been placed on the importance of anterior hip coverage by not only joint surgeons [2,5,6] but also pediatric orthopedic surgeons [3,7] and sports medicine surgeons [8][9][10], especially for borderline hip dysplasia [3,9,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted by hip surgeons that the anterior center edged angle (ACEA) measured on FP radiographs can be utilized in determining the anterior coverage of the hip joint, although there is one study that found that the ACEA (measured by a different method) may have limited ability to predict threedimensional coverage of the femoral head in patients with developmental dysplasia of the hip [25]. An association between ACEA and clinical outcomes has been revealed in previous studies [3,9,12,[26][27][28][29], with it being a powerful predictor of a surgery [3].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Following the increasing understanding of the 3D morphology of the hip joint, an increasing emphasis has been placed on the importance of anterior hip coverage by not only joint surgeons [1,4,5] but also sports medicine surgeons[6-8] and pediatric orthopedic surgeons [2,9], especially for borderline hip dysplasia. [2,7,[10][11][12] An accurate measurement of anterior hip coverage is crucial to determine whether patients with hip dysplasia need hip preservation surgery. It is also a crucial factor in estimating the outcome of hip preservation surgery.…”
Section: Introductionmentioning
confidence: 99%